Marketing Analysis of Innovation Products in Social Media Market Orientation - Ferdi Antonio; Luh Komang Candra Dewi; Heny Hidayati; Donny Dharmawan; Agus Nurofik (Indonesian Journal Economic Review (IJER), 2026)
The purpose of this study is to analyze the obstacles and solutions regarding the marketing analysis of innovation products in social media market orientation. The method used in this study is a qualitative descriptive method. This method is supported by comprehensive secondary data sourced from theoretical books and theoretical practices in journal articles. The research results show that marketing analysis of innovation products in social media market orientation is a crucial approach in the digital era. When companies launch innovative products, whether in the form of new features, environmentally friendly products, or new culinary concepts, social media is no longer just a promotional channel, but rather a strategic ecosystem for understanding and responding to the market. Marketing innovative products within a market-oriented framework on social media requires a radical transformation in how companies interact with their audiences, shifting the focus from simply showcasing advanced features to truly meeting consumers' emotional and functional needs. The most crucial initial step is building a deep, data-driven understanding through active social listening to capture emerging conversations, complaints, and hidden trends within the community.